جمالية العنوان في الخطاب الشعري النسوي نماذج مختارة من ديوان سمية محنش "مسقط قلبي" - بريش, أم الخير هناء; بتقة, سليم (جامعة الوادي - University of Eloued, 2023)
يهدف هذا المقال إلى استجلاء جمالية العنوان في الخطاب النسوي الجزائري، متخذين من ديوان "مسقط قلبي" باكورة الشاعرة "سمية محنش" الإبداعية نموذجا للدراسة. وقد استقصينا في هذا المقال البحث عن الآثار الجمالية التي تولدها عناوين القصائد المنتقاة عبر مقاربة تستعير آليات المنهجين السيميائي والأسلوبي وتنفتح على التأويل. This article aims to clarify the aesthetics of the title in the Algerian feminist discourse, taking the collection of "My Heart's Hometown" the first creative poet "Somia Mehanneche" as a model for the study. In this article, we investigated the search for the aesthetic effects generated by the titles of the selected poems through an approach that borrows the mechanisms of the semiotic and stylistic approaches and is open to interpretation..
The Aesthetics Of The Title In The Feminist Poetic Discourse Selected Models From Somia Mehanneche's Diwan "my Hometown"
Keywords: خطاب نسوي، سمية محنش، تأنيث الذاكرة، مسقط قلبي.; feminist discourse,Somia Mehanneche, memory feminization , my hometown